Impact of shoreline changes to pahang coastal area by using geospatial technology - Fazly Amri Mohd; Khairul Nizam Abdul Maulud; Rawshan Ara Begum; Siti Norsakinah Selamat; Othman A. Karim (Penerbit Universiti Kebangsaan Malaysia, 2018)
Malaysia has a long coastline stretching over 4,809 km where more than 1,300 km of beaches are experiencing erosion. Coastal erosion is recognised as the permanent loss of land and habitats along the shoreline resulting in the changes of the coast. Thus, it is important to detect and monitor shoreline changes especially in Pahang coast by identifying the rate of shoreline erosion and accretion. This study used temporal data and high spatial resolution imagery (SPOT 5) using remote sensing and GIS techniques to monitor shoreline changes along 10 study locations, which is from Cherating to Pekan of the Pahang coast. The total length of shoreline changes is about 14 km (14035.10 m) where all these areas are very likely to experience erosion ranging from 0.1 to 94.7 ha. On the other hand, these coastal areas found a minimal accretion with increased sediment from 0.1 to 2.8 ha. Overall, the coastal areas are exposed to higher erosion process than accretion with a very high vulnerability of erosion rate from 1.8 to 20.9 meter per year. The findings on monitoring shoreline changes and identifying vulnerable erosion areas might be useful in the policy and decision making for sustainable coastal management.